ARTIKULASI KEPENTINGAN MASYARAKAT HUKUM ADAT KENEGERIAN KUNTU DALAM MENGEMBALIKAN STATUS ULAYAT TAHUN 2018 - Nurhanifa "; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Rights Society customary law customary right for land in fact have been confessed in Decision Lawcourt of Konstitsui Number 35 Year 2012. But at its implementation not yet maximal so that customary law society still not yet obtained surely by right of its customary right for land with effort articulate importance which not yet obtained efficacy.This research aim to for Articulatory mendeskripsikan of Society Customary Law Eeriness Of Kuntu In Returning Status Customary right for land and to know resistor factors not yet reached of confession of customary right for land rights by Local Government Of Sub-Province Camphor. Location Research done by in Country of Kuntu. Hereinafter, data collecting technique dont with documentation and interview.Result of this research in Articulation Have Interest Society Customary Law Eeriness of Kuntu in returning Customary right for land status not yet been reached to through Direct Delegation, Personal Link, Institutional Channel, and Demonstration. The mentioned because of lack of compactness ( cohesion group), product inexistence punish Sub-Province Camphor area about customary right for land land ground   Keyword: Articulatory of Importance, Direct Delegation, Personal Link, Institutional Channel, Demontrasi.